Ittijah Tafsir Falsafi: Analisis Tafsir Penciptaan Alam Menurut Imam Al-Ghazali dan Al-Farabi - Pebriani Srifatonah; Siti Aminah; Eni Zulaiha (Definisi: Jurnal Agama dan Sosial Humaniora, 2023)
One of the models for the interpretation of the Qur'an is the ittijah of philosophical interpretation, which emerged in the Middle Ages or during the heyday of Islamic scholarship related to philosophy and religion. Some scholars say that philosophical thought cannot be reconciled with religion. Because philosophy is the result of human thought, while religion comes from God. This article tries to analyze the thoughts of Ibn Rushd and Imam Ghazal when explaining in the interpretation of verses related to the world of Qadim. Furthermore, the researcher will apply qualitative methods in compiling this writing, where the results of this research are related to the idea of philosophical interpretation in which the form of interpretation of the verses of the Qur'an uses philosophical thoughts or views. This cannot be distinguished from the views of the scholars regarding this philosophical interpretation in their journey. In this ittijah interpretation, the scholars have different opinions. First, a group of scholars who accept the existence of a philosophical interpretation such as Ibn Rushd and al-Farabi, and the next group is a group that disagrees with ittijahfalsaf, namely al-Ghazali and ar-Razi. In this study, researchers mainly focus on the debate between the advantages and disadvantages of the interpretation of the philosophical ittijah dedicated to the interpretation of al-Ghazali and al-Farabi.